2018
DOI: 10.3390/inventions3010011
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Setup to Perform 3D Locomotion Tracking in Zebrafish by Using a Single Camera

Abstract: Generally, the measurement of three-dimensional (3D) swimming behavior in zebrafish relies on commercial software or requires sophisticated scripts, and depends on more than two cameras to capture the video. Here, we establish a simple and economic apparatus to detect 3D locomotion in zebrafish, which involves a single camera capture system that records zebrafish movement in a specially designed water tank with a mirror tilted at 45 degrees. The recorded videos are analyzed using idTracker, while spatial posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 63 publications
(82 reference statements)
0
45
0
Order By: Relevance
“…Three-dimensional (3D) locomotion is a sensitive tool for the risk assessment of the alteration of swimming behavior after exposure to chemicals or pollutants [24]. It was found that 50 ppb PbCl 2 -treated zebrafish had the lowest average speed ( Figure 2B) and average angular velocity ( Figure 2C).…”
Section: Lead Exposure Induced Anxiety-like Behavior In Zebrafishmentioning
confidence: 99%
See 2 more Smart Citations
“…Three-dimensional (3D) locomotion is a sensitive tool for the risk assessment of the alteration of swimming behavior after exposure to chemicals or pollutants [24]. It was found that 50 ppb PbCl 2 -treated zebrafish had the lowest average speed ( Figure 2B) and average angular velocity ( Figure 2C).…”
Section: Lead Exposure Induced Anxiety-like Behavior In Zebrafishmentioning
confidence: 99%
“…Three-dimensional locomotor activity was tracked at four time points, including 1, 4, 7, and 14 days after the exposure to PbCl 2 , according to a previously described protocol [24]. The 3D locomotion test of six fish was performed using an acrylic tank (20 cm × 20 cm × 20 cm dimension with 15 cm water level).…”
Section: Zebrafish 3d Locomotor Activity Testmentioning
confidence: 99%
See 1 more Smart Citation
“…These behavior tests were started with a three-dimensional (3D) locomotor activity test that tracked the detailed trajectories. This assay was reported as a highly sensitive method to evaluate the potential chemical toxicity in fish behavior [38,39]. After a 15-min acclimation in the experiment tank, the lpar3 KO fish showed similar behavior with the control fish in terms of their locomotor activity as indicated by similar average speed, freezing time movement ratio, and rapid movement ratio (Figure 2A,E,F).…”
Section: Lpar3 Ko Zebrafish Displayed Abnormal Exploratory Behavior Imentioning
confidence: 79%
“…The behavior tests were as follows: novel tank, shoaling, mirror biting, social interaction, predator avoidance, color preference, and three-dimensional (3D) locomotion tests. Three-dimensional locomotor activity was measured by using an acrylic tank (20 cm × 20 cm × 20 cm) with~6 L water according to a previously described protocol [39]. The novel tank, mirror biting, predator avoidance, social interaction, and shoaling tests were performed by a designed zebrafish tower consisting of ten trapezoid test tanks (28 cm × 5 cm × 15 cm) with~1.25 L water in each according to our previously published protocols [40].…”
Section: Zebrafish Adult Behavioral Assessmentmentioning
confidence: 99%